Have the Issues in Community Forestry Changed Over the Past Decade? A Case Study from Mid-hills of Nepal - Lamichhane, Sabina; Lamichhane, Yub Raj; Upadhyaya, Anju; Lamichhane, Sanjeev (Janaprakash Journal of Multidisciplinary Research, 2025)
Nepal is widely recognized as a pioneer in community forestry, with its remarkable contributions to improving forest cover, enhancing biodiversity, empowering local communities, and supporting rural livelihoods. Despite these contributions, the community forests (CF) of Nepal have continuously faced issues and challenges since their inception, among which conflict remains a persistent issue. This study examines the issues of conflict in CF over time by comparing the conflict situation in 2013 and 2024 in Saunepani Bareli CF, Kaski district. The study employed a Focused Group Discussion (FGD) and Key Informant Interview (KII) for primary data collection, supplemented by a review of published journal articles and reports, for secondary data collection. The findings revealed that the major issues remain similar to those identified a decade ago, but with different dimensions. There are notable changes in leadership, benefit sharing, and governance. Users show limited interest in the leadership position, have reduced dependency on the forest, and compromised governance practices. Moreover, a decline in interest of users in CF activities has resulted in passive forest management. In this regard, the study recommends initiating forest-based income and employment-generating initiatives to revitalize users towards community forestry activities.